Women's mobilization and gender outcomes in transitions to democracy: the case of South Africa - Waylen, Georgina (2007)
This article explores the conditions under which women's mobilizations during transitions to democracy can achieve some of their aims. It broadens the comparative analysis of gender and transitions undertaken to date by looking at a case in which gender outcomes, measured in terms of women's descriptive and substantive representation, have been relatively positive. Unusually women, organized as women, had some input into the negotiations during the South African transition. The article argues that a complex interaction of variables contributed to the achievement of certain positive gender outcomes. A broad women's coalition, the Women's National Coalition, did play an important role. However, two other sets of factors - a favorable political opportunity structure and the strategic actions and alliances of certain key women actors - made a crucial contribution to its effectiveness in influencing this transition, as women's mobilization on its own is no guarantee of success. - Reproduced.
Keywords: Women - South Africa; Women